Doomed to the Empire. A Vision of the Russian Historical Path in Alexander Pushkin’s The Bronze Horseman - Bortnowski, Antoni (Poznańskie Studia Slawistyczne, 2023)
The article is an attempt to explore the vision of Russian history in Alexander Pushkin’s The Bronze Horseman. The key role in the poem is played by the figure of Peter I, who is shown as a despot on the one hand, and a bold visionary on the other. In The Bronze Horseman, Pushkin presents a suggestive image of the flood in St. Petersburg, referring to such problems as the clash between an ordinary man and history or the essence of rebellions and revolutions. Deciphering the meaning of individual motifs allows us to perceive Pushkin’s coherent and multidimensional historiosophical vision. The main conclusion of the article is the statement that Russian imperialism in The Bronze Horseman is shown as an organic element of Russianness, without which Russia could not have formed as a strong and modern state. Moreover, the poem can invariably be seen as a key to understanding the essence and vitality of Russian imperialism.